Different core-specific T cell subsets are expanded in chronic hepatitis C with advanced liver disease. (December 2019) - Cachem, Fabio C.O.F.; Dias, Aleida S.; Monteiro, Clarice; Fernandes, Gabriel; Delphim, Letícia; Tavares, Felipe; Maciel, Alessandra M.A.; Amendola-Pires, Marcia M.; Brandão-Mello, Carlos Eduardo; Andrade, Regis Mariano; Bento, Cleonice A.M.
Highlights: IL-17 + IL-6 + T-cells are elevated in HCV patients with advanced liver stiffness. Lower percentage of CD39 + Tregs in HCV patients with advanced liver stiffness. HCV-specific PD-1 + CD57 + T cells accumulate in patients with worse hepatic lesions. Abstract: Chronic hepatitis C (CHC) is frequently related to liver fibrosis, and several studies have suggested that the immunological activity of HCV antigens contributes to hepatic damage. In the present study, among structural and non-structural HCV antigens, elevatedIL-1β, IL-6, IL-17 levels were secreted by PBMC cultures obtained from CHC patients following stimulation with core antigen. Moreover, the percentage of core-specific IL-6 + IL-17 + (CD4 + and CD8 + ) T cells was significantly higher in patients with worsehepatic lesions, determined on the Metavir scale. When compared with healthy subjects, the percentage of circulating Treg cells was elevated in CHC patients, mainly among those with advanced liver fibrosis. Nevertheless, in this last group of patients, the proportion of CD39 + Treg subsets was very low. Finally, the percentage of senescent (CD57 + CD28 − ) and exhausted (PD-1 + CD28 + ) core-specific T cells in CHC patients was also found to be a result of fibrotic hepatic status. In summary, imbalances between different core-specific T cell subsets are associated with liver fibrosis severity.